Receptor Tyrosine Kinases: Structure, Functions and Role in Human Disease - Wheeler, Deric L.; Yarden, Yosef; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
Receptor tyrosine kinases (RTKs) play critical roles in embryogenesis, normal physiology and several diseases, and over the last decade have become the number one targets of cancer drugs. Receptor Tyrosine Kinase: Structure, Functions and Role in Human Disease systematically covers, for the first time, the shared structural and functional features of the RTK family. Understanding the evolutionary origin of the 58 RTKs, their roles in invertebrates and in humans, as well as downstream signaling pathways, is essential for fundamental research and for attempts to develop pharmacological agents able to enhance or intercept their actions. The assembly of chapters written by experts underscores commonalities and is an ideal companion volume to The Receptor Tyrosine Kinase Family, which refers to specific subfamilies of RTKs, along with their unique landmarks.
The Eukaryotic Protein Kinase Superfamily -- Evolution of Receptor Tyrosine Kinases -- RTKs in Invertebrates: Lessons in Signal Transduction -- Cell Signaling by Receptor Tyrosine Kinases -- Nuclear Signaling of Receptor Tyrosine Kinases -- Computational and Modeling Aspects of RTK Networks -- Endocytosis of Receptor Tyrosine Kinases -- Structural Features of the Ligand-Binding Extracellular Domain -- Structural Features of the Kinase Domain -- Targeting RTKs in Cancer.-  Mouse Models of Receptor Tyrosine Kinases.
Keywords: Cell biology; Proteins .; Cancer research; Cell Biology; Receptors; Cancer Research